The Evolution of Multicultural Education Indonesia 2000-2022: Bibliometric Analysis, Google Scholar - Tria Ina Utari (J-MPI (Jurnal Manajemen Pendidikan Islam), 2023)
The complexity of Indonesia's diversity and cultural patterns have undergone a major evolution, especially with multicultural education in several parts of Indonesia. Multicultural education is an echo of the government in maintaining peace between ethnicities, races, and religions in Indonesia. The purpose of this study is to conduct a bibliometric analysis of Google Scholar articles about the evolution of multicultural education trends in Indonesia by searching for 2000-2022 through the productivity of scientific articles, productive authors, thematic mapping, the emergence of shared keywords, and the collaboration of authors. This analysis uses Vos viewer software. This study managed to collect 994 articles, and 32,497 citations, with an author/paper ratio of 1.81. Multicultural research in Indonesia came to the fore in 2002 and continues to increase sharply in 2020, 2021, and 2022. The first-ranked researcher for the past 22 years is Wekke with 11 articles published, while the highest h-index is C Mahfud in 2013 with an h-index of 1475, he wrote a multicultural educational book. Multicultural education resulted in 4012 links, with several titles and abstracts related to it. The originality in this study as far as is known has never been done, especially how the evolution of multicultural education in Indonesia by utilizing artificial intelligence technology.